2020
DOI: 10.1017/s1368980020001081
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of infant and young child feeding practices in rural Rwanda

Abstract: Abstract Objective: To explore and gain an in-depth understanding of the factors influencing child feeding practices among rural caregivers in Rwanda. Design: In-depth semi-structured qualitative interviews were conducted. Purposive sampling was used to recruit pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Previous studies conducted in Rwanda showed that children were introduced to complementary foods later than recommended (i.e., aged 8 months), 13 and that dilute cereal porridges were the main food given to young children who were aged 2-8 months. 53 A recent study 33 conducted in the same population also found that thin porridges and stews/soups were the most common foods given to young children, and that the consistency of these foods hindered the use of MNP. In addition, MNP must be mixed with thick solid or semisolid complementary foods because it dissolves in liquids, which may change the taste or color of the foods, leading to less acceptance by children.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies conducted in Rwanda showed that children were introduced to complementary foods later than recommended (i.e., aged 8 months), 13 and that dilute cereal porridges were the main food given to young children who were aged 2-8 months. 53 A recent study 33 conducted in the same population also found that thin porridges and stews/soups were the most common foods given to young children, and that the consistency of these foods hindered the use of MNP. In addition, MNP must be mixed with thick solid or semisolid complementary foods because it dissolves in liquids, which may change the taste or color of the foods, leading to less acceptance by children.…”
Section: Discussionmentioning
confidence: 98%
“…We adjusted for these variables because our previous research in the same population showed that child illness has negative effects on how mothers feed their children, including withholding or restricting some foods from children's diets. 33 Unadjusted and adjusted odds ratios (OR) and 95% confidence intervals (CI) were computed. Variables with a P value of <.05 were considered significant predictors.…”
Section: Quantitative Datamentioning
confidence: 99%
“…The Rwanda demographic and health survey 2014-2015 shows that the number of children 6-23 months old who meet the recommended minimum acceptable diet has remained almost the same between 2010 and 2015 (from 17 to 18%). Past qualitative studies on IYCF practices in Rwanda have mainly focused on understanding why mothers do not practice the recommended IYCF practices [14,15]. Factors that include mother's perception of breastmilk insufficiency, excessive workload for the mother, poverty, food insecurity, and lack of support from significant family members were the most commonly reported challenges [14].…”
Section: Introductionmentioning
confidence: 99%
“…Four qualitative studies looked at community solutions to malnutrition in a novel and participatory approach with the population (13)(14)(15)(16) , while one study looked at factors influencing the implementation of a multisectoral, community-level nutrition programme aimed at improving infant and young child feeding practices (17) . The other qualitative studies explored nutritionrelated behaviours of mothers (18,19) , women outside of their maternal role (20) , parents (21) , and adolescents (22) .…”
mentioning
confidence: 99%
“…Infant feeding is reported to be strongly influenced by family matriarchs in South Africa, although the advice given is not aligned with infant and young child feeding recommendations (18) . The conflict between traditional knowledge on infant feeding and information provided by health workers is also highlighted in a study in Rwanda (19) . The importance of social media as source of nutrition information and determinant of food choices is reflected in a study in Ghana (20) .…”
mentioning
confidence: 99%